Chemical Characteristics of Precipitation in a Typical Urban Site of the Hinterland in Three Gorges Reservoir, China - Liuyi Zhang; Baoqing Qiao; Huanbo Wang; Mi Tian; Jian Cui; Chuan Fu; Yimin Huang; Fumo Yang (Journal of Chemistry)
Major water-soluble ions were analyzed for two-year precipitation samples in Wanzhou, a typical urban site of the hinterland of Chinese Three Gorges Reservoir. The pH values of the precipitation were in the range of 4.0 to 8.3, and the volume-weighted mean (VWM) value was 5.0. The concentration order of anions and cations was as follows: SO42->NO3->Cl->F- and NH4+>Ca2+>Na+>K+>Mg2+, respectively. Good correlations were found between SO42- and NH4+, SO42- and Ca2+, NO3- and NH4+, and NO3- and Ca2+, implying their co-occurrence in the precipitation, most likely as (NH4)2SO4, (NH4)HSO4, NH4NO3, CaSO4, and Ca(NO3)2. The sum of all measured ions was 416.4 μeq L−1, indicating serious air pollution in Wanzhou. NH4+ and Ca2+ were the most important ions neutralizing the acidic compounds in the precipitation; their major sources included agricultural activity and crustal dust. Local anthropogenic activities, for example, coal burning and traffic related sources, contributed most of SO42- and NO3-. The equivalent concentration ratio of SO42-/NO3- was 4.5, indicating that excessive emission of sulfur was the main reason leading to the precipitation acidity in Wanzhou. However, this ratio was lower than the ratio (5.9) in 2000s in Wanzhou, indicating that the contribution of nitric acid to the acidity of precipitation was strengthening.